Location of upstream and downstream industries - Pontes, José Pedro (2010)
This paper studies the issue of agglomeration versus fragmentation of vertically related industries. While the downstream industry works under perfect competition, the upstream industry is a duopoly where each firm supplies a differentiated input to the competitive firms. These process the inputs under a quadratic production function entailing decreasing returns as in PENG, THISSE and WANG (2006). It is found that fragmentation occurs if the transport cost of final goods is medium to high, while the transport cost of inputs is low. Otherwise, agglomeration prevails. Multiple agglomerated equilibria are possible if the transport cost of intermediate goods is either medium or high.